6. REPRESENTASI PEREMPUAN DALAM ADABUL MUQAWAMAH UNTUK PERJUANGAN PALESTINA ( KAJIAN HISTORIS) - FITRI LIZA (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2022)
In the context of Palestinian Arabic literature, poetry is a reflection of the life of the Palestinian people in terms of social, cultural, economic and political issues. The Israeli occupation has caused deep wounds and suffering to the Palestinian people. Of the 17 names mentioned, Fadwa Tuqan represents the presence of women in voicing what the Palestinian people feel. Fadwa Tuqan is a strong woman who quickly understands what is happening in her homeland. From that Fadwa Tuqan, who lived in two wars, realized his love for Palestine. When he was born and grew up, he witnessed the British rule over Palestine, and when he began to grow up and understand life, he witnessed the Arab people trying to fight and strive for freedom and independence and take back the glory of Palestine at all costs.